(3TQM GdeMQQs - (3jMji Hf TQa Hf eQj Hf MSf GdMRGej GdMhQGfj, Gdfhhj, GdTGaYqj, CHh RcQjG, eMjj GdOjf, (B676 (3g` s; (3YHO GdcQje Hf eMeO Hf YHO GdcQje, CHh GdbGSe GdQGaYj GdbRhjfj,J (B623 (3g` s ((3eOjfI HdHjS s)
(3ChdgG (B:s
(3GdMeO ddg GdHQ GdLhGO CeG HYO aEf GdETJZGd HGdYde ef CaVd GdUfGYGJ hGJbi eNJUQ GdeMQQ ddEeGe CHj GdbGSe GdQGaYi s
(3BNQgG (B:s
(3hYJb GdeSJhdOI ef QCS GdeGd hHGddg GdJhajb fLR GdcJGH s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3CJe TQMg (B669s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B55 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B3s
Keywords: (3Gdabg GdTGaYjs